To Evaluate The Adoption Of Advance Endodontic Technology By General Dental Practitioner In Gujarat – A Questionnaire Survey (Journal of Pharmaceutical Negative Results, 2022)
Background: The ability to achieve an appropriate seal and the stability of the optical qualities over time are the essential requirements for adhesive aesthetic materials. Aim: To assess and compare the occlusal and gingival margin sealing characteristics of total etch and universal adhesive systems in class V restorations, along with the impact of chlorhexidine disinfectant on bonding system microleakage. Material and methods: 60 premolar teeth were selected in this in vitro study. Teeth were divided into three separate groups (20 in each group), and further divided into 2 subgroups with control and Chlorhexidine application group. 3 different Adhesive bonding agents: (1) Single Bond Universal (3M ESPE), (2) One Coat 7 Universal (Coltene) (3) Tetric-n-bond (Ivoclar Vivadent), were assessed. Samples were passed through a dye leakage test. A stereomicroscope was used to assess microleakage. To evaluate the variation in microleakage among different adhesives, data were analysed using Kruskal-Wallis, Post-hoc Tukey test, and Chi square test. Results: The microleakage was more at the gingival margin. At the occlusal margin significant difference was found. Single bond universal performed better overall. Effect of chlorhexidine was significant only at occlusal margins as compared to gingival margins. Conclusions: Compared to total etch adhesive, universal agents as self-etch adhesives showed lower microleakage. Effect of chlorhexidine does reduce microleakage, more significant at occlusal margins.